Annual Report of the Committee on Gynecologic Oncology, Japan Society of Obstetrics and Gynecology: Patient Annual Report for 2014 and Treatment Annual Report for 2009. Issue 11 (11th September 2017) - Saito, Toshiaki; Takahashi, Fumiaki; Katabuchi, Hidetaka; ,
Abstract: The Japan Society of Obstetrics and Gynecology collects and analyzes annual data on gynecologic cancers from member institutions. We present the Patient Annual Report for 2014 and the Treatment Annual Report for 2009. Data on 7436 patients with cervical cancer, 9673 with endometrial cancer, 5924 with ovarian cancer, and 1909 with ovarian borderline tumor for whom treatment was initiated in 2014 were summarized in the Patient Annual Report. Stage I accounted for 55.6%, stage II for 22.9%, stage III for 10.2%, and stage IV for 11.2% of all patients with cervical cancer. Stage I accounted for 72.3%, stage II for 6.0%, stage III for 14.1%, and stage IV for 7.7% of all patients with endometrial cancer. Stage I accounted for 43.3%, stage II for 9.1%, stage III for 27.6%, and stage IV for 7.2% of all patients with ovarian cancer. Data on the prognosis of 4126 patients with cervical cancer, 4613 with endometrial cancer, and 3205 with ovarian cancer for whom treatment was initiated in 2009 were analyzed in the Treatment Annual Report. Survival was analyzed by using the Kaplan–Meier method, the log–rank test and the Wilcoxon test. The 5‐year overall survival rates for patients with cervical cancer were 92.4% for stage I, 76.7% for stage II, 54.3% for stage III, and 25.2% for stage IV. The equivalent rates for patients with endometrial cancer were 94.6%, 89.4%, 78.3%, and 25.0%, respectively; and those for patients with ovarian cancer (surface epithelial–stromal tumors) were 90.5%, 78.8%, 46.0%, and 25.1%, respectively.